Analysis of Conservative Thinking Characteristics of Islamic Faith and Philosophy Students in West Sumatra - Amril Amril; Ermagusti Ermagusti; Dewi Derita Hayati (Universitas Islam Negeri Imam Bonjol Padang, 2022)
It is common for students of the Islamic Faith and Philosophy (IFP) Study Program to have a philosophical character because they are formed with a rational, systematic, universal, critical, and radical mindset. However, some students of the IFP Study Program have conservative reasoning. This study analyzes IFP Study Program students in West Sumatra who have conservative thinking characteristics. This research is qualitative with the methods of description, interpretation, and analysis. This study found data that 27% of IFP Study Program students in West Sumatra had conservative thinking characteristics; 2% of them are in the very conservative category and 25% of them are in the conservative category. IFP Study Program students with conservative thinking characteristics believe that the Salafis shalihin generation is the best generation and imitates the attitudes, behaviors, and actions of the Prophet Muhammad SAW. both as a prophet and as a human being. The factors that cause IFP Study Program students to have conservative thinking characteristics are education history, reading books, and the environment